Willingness to Pay for Agricultural Environmental Safety: Evidence from a Survey of Milan, Italy, Residents - Chiara M. Travisi; Peter Nijkamp (Fondazione Eni Enrico Mattei (FEEM), 2004)
The widespread use of pesticides in agriculture provides a particularly complex pattern of multidimensional negative side-effects, ranging from food safety related effects to the deterioration of farmland ecosystems. The assessment of the economic implications of such negative processes is fraught with many uncertainties. This paper presents results of an empirical study recently conducted in the North of Italy aimed at estimating the value of reducing the multiple impacts of pesticide use. A statistical technique known as conjoint choice experiment is used here in combination with contingent valuation techniques. The experimental design of choice modelling provides a natural tool to attach a monetary value to negative environmental effects associated with agrochemicals use. In particular, the paper addresses the reduction of farmland biodiversity, groundwater contamination and human intoxication. The resulting estimates show that, on average, respondents are prone to accept substantial willingness to pay premia for agricultural goods (in particular, foodstuff) produced in environmentally benign ways.
Keywords: C42; H23; I12; Q24; 330; Pesticide risks; Food safety; Willingness-to-pay; Choice modeling; Contingent valuation; Lebensmittelsicherheit; Pestizid; Umweltbelastung; Zahlungsbereitschaftsanalyse; Landwirtschaft